HUBUNGAN TINGKAT PENDIDIKAN GURU DENGAN KOMUNIKASI EFEKTIF DALAM PEMBELAJARAN TK SE KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - ', Mirawati; Indarto, Wusono; Novianti, Ria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims 1) To determine the level of teacher education in kindergarten Se District of Marpoyan Peace Pekanbaru. 2) To determine the effective communication in learning in kindergarten Se District of Marpoyan Peace Pekanbaru. 3) To determine the level of teacher education relationship with effective communication in learning in kindergarten Se District of Marpoyan Peace Pekanbaru. The method used in this research is the correlation method. The population of this study was 284 teachers in kindergarten Se District of Marpoyan Peace Pekanbaru City came from 39 TK. The sampling is random sampling Sample is taking members of the sample taken randomly without regard to strata that exist in this population. Based on the formula, the sample in this study were as many as 74 teachers. The data collection techniques used are questionnaire (questionnaire). Data were analyzed by using quantitative research and data analysis techniques using techniques konferensial. The study hypothesis was sifnifikan There is a positive relationship between level of education and teachers with effective communication in learning in kindergarten Se District of Marpoyan Peace Pekanbaru. Based on the research results, we can conclude there is no significant correlation with the level of teacher education in learning effective communication in kindergarten Se District of Marpoyan Peace Pekanbaru City Riau province with a contribution amounting to 0.3522 relationship. That is, the education of teachers with the ability to communicate have a low correlation in the delivery of learning in kindergarten. Key Words: Level of education, effective communication.